Beyond the Shadows: a Public Theology of Disability Inclusion - Gould, James (International journal of public theology, 2024)
This paper presents a public theology affirming the normalization of adults with intellectual and developmental disabilities. Religious convictions about human equality and social justice contribute constructively to matters of public concern. While official principles of disability services do, operating practices often do not, accord with a theological vision of God’s desire for human flourishing. The analysis summarizes what is going on (many adults with intellectual and developmental disabilities experience restricted lives), employs socio-ecological theory to explain why (shortcomings at multiple levels of civil society disadvantage them), uses theology and sociology to specify what should be going on (they should be able to live ‘normal’ lives like non-disabled people) and proposes action steps (change in numerous social systems can promote normalization).